VITASENIOR-MT: A distributed and scalable cloud-based telehealth solution - Mendes, Diogo (2019)
VITASENIOR-MT is a telehealth platform that allows to remotely monitor biometric and environmental data in a domestic environment, designed specifically to the elderly population. This paper proposes a highly scalable and efficient architecture to transport, process, store and visualize the data collected by devices of an Internet of Things (IoT) scenario. The cloud infrastructure follows a microservices architecture to provide computational scalability, better fault isolation, easy integration and automatic deployment. This solution is complemented with a pre-processing and validation of the collected data at the edge of the Internet by using the Fog Computing concept, allowing a better computing distribution. The presented approach provides personal data security and a simplified way to collect and present the data to the different actors, allowing a dynamic and intuitive management of patients and equipment to caregivers. The presented load tests proved that this solution is more efficient than a monolithic approach, promoting better access and control in the data flowing from heterogeneous equipment.